TRPM3 in the eye and in the nervous system: from new findings to novel mechanisms - Behrendt, Marc (Biological chemistry, 2022)
The calcium-permeable cation channel TRPM3 can be activated by heat and the endogenous steroid pregnenolone sulfate. TRPM3’s best understood function is its role as a peripheral noxious heat sensor in mice. However, the channel is expressed in various tissues and cell types including neurons as well as glial and epithelial cells. TRPM3 expression patterns differ between species and change during development. Furthermore, a plethora of TRPM3 variants that result from alternative splicing have been identified and the majority of these isoforms are yet to be characterized. Moreover, the mechanisms underlying regulation of TRPM3 are largely unexplored. In addition, a micro-RNA gene (miR-204) is located within the TRPM3 gene. This complexity makes it difficult to obtain a clear picture of TRPM3 characteristics. However, a clear picture is needed to unravel TRPM3’s full potential as experimental tool, diagnostic marker and therapeutic target. Therefore, the newest data related to TRPM3 have to be discussed and to be put in context as soon as possible to be up-to-date and to accelerate the translation from bench to bedside. The aim of this review is to highlight recent results and developments with particular focus on findings from studies involving ocular tissues and cells or peripheral neurons of rodents and humans.
Gesehen am 14.11.2023